Desain lanskap jalan (Studi Kasus Jalan Dr. Muwardi Denpasar) - Anggoro, Bramantyo Wahyu; Sukewijaya, I Made; Asmiwyati, I Gusti Agung Ayu Rai (Jurnal Arsitektur Lansekap; Vol.8, No.2, Oktober 2022, 2022)
Street in urban areas has an important function to support human activity and social interaction. That matter can be achieved by a good streetscape planning based on regulations and standards for streetscape design. The aim of streetscape planning is to give safety and amenities for street user in urban area. This research took place in Dr. Muwardi street Denpasar. Dr. Muwardi street’s located inside Denpasar City civic center well known as Niti Mandala area. Lack of streetscape planning makes street activities unorganized. A number of street vendors that attract visitor with personal transportation caused a street dysfunction. This study aims to design a good streetscape, and optimize the potential and solve the problems in Dr. Muwardi street. The research used a descriptive qualitative methode through inventory, analysis, synthesis, concept making, planning, and pre-design phase. The result shown that the street design was devided into trading space, pedestrian space, and traffic space. Trading spaces organized by rearrange the street vendor trading zone. Pedestrian space designed by adding sidewalk and street amenities, meanwhile traffic area designed by adjusting streetscape standart into the site. To enchance local characteristic and aesthetic value to the streetscape, additional street landscape trees from Gumi Banten plant list is applied.